Evolution of different designs and wear studies in total hip prosthesis using finite element analysis: A review. Issue 1 (31st December 2022) - K N, Chethan; Bhat N, Shyamasunder; Zuber, Mohammad; Shenoy B, Satish
Abstract: In replacement surgery of the hip joint, an implant is replaced into the natural femur which recreates the articulation and functionally of a natural joint. Total hip replacement is significantly increasing by the day worldwide and is likely to increase by 174% by 2030. Primary revision is another major concern for total hip replacement with revision rates likely to increase by 137%. The first part of the article states the basic anatomy of the hip joint, different ligaments in the hip, the disorders associated with the joint, and evaluation of total hip arthroplasty. In the second part some of the major works are highlighted followed by a detailed discussion about different design considerations and wear-related issues in hip joints. More emphasis is given to the tribological behavior of implants under different conditions. The design aspects and several parameters which affect the wear rate in implants are summarized. Also, different testing methods which are used both in experimental and numerical techniques are reported to estimate the wear rates in hip implants with the evolution of hip implants since the early 20 th century, in terms of different designs, materials and wear hip implant arthroplasty is known as one of the best advancements in healthcare. Further research is needed to establish to improve the life expectancy of hip implants.